Predictors of dropping out from a home tele-exercise programme: A cohort study derived from a randomised controlled trial - Gustavo Yuki; Luiz Hespanhol; Lisa Mohr; Adelle Kemlall Bhundoo; David Jiménez-Pavón; Bernhard Novak; Stefano Nuccio; Jose Daniel Jiménez García; Julian David Pillay; Lorenzo Rum; Celso Sánchez Ramírez; Lutz Vogt; et al. (Tabriz University of Medical Sciences, 2024)
Background: Online home exercises represent opportunities to increase physical activity levels. However, high dropout rates are commonly reported in such programmes. This study aimed to investigate the predictors of dropping out from an online home exercise programme. Methods: A total of 760 individuals from nine countries participated in this 8-week prospective cohort study derived from a randomised controlled trial. The participants were randomised into "4-week live-streamed exercise ->4-week recorded exercise" or "4-week no intervention ->4-week recorded exercise" group. Repeated measurements using weekly questionnaires were performed. Pain intensity, disability, mental well-being score, exercise motivation, sleep quality, impulsiveness/anxiety, and physical activity level were analysed. Results: A total of 53.8% (95% confidence interval [CI] 50.3%-57.3%) participants dropped out from the programme. The identified predictors of dropping out from the programme were: well-being (odds ratio [OR] 0.94, 95% CI 0.91-0.97) and disability (OR 1.02, 95% CI 1.002-1.04) at baseline considering the first 4 weeks; age (0.98; 95% CI 0.96-1.00) and baseline well-being (0.93; 95% CI 0.89-0.97) considering the entire follow-up (8 weeks); exercise motivation (0.92; 95% CI 0.87 to 0.97) and general impulsiveness/anxiety (1.04; 95% CI 1.01-1.07) repeated measured over time. Conclusion: About half of the participants dropped out from the online home exercise programme. Higher baseline scores in mental well-being and age predicted a reduction in dropping out. Higher baseline disability predicted an increase in dropping out. During the follow-up, higher exercise motivation was associated with a reduction in dropping out, and higher impulsiveness and anxiety were associated with an increase in dropping out.